STRATEGI GURU TAHFIDZ DALAM MENINGKATKAN KEMAMPUAN MENGHAFAL JUZ 30 SISWA SMA ISLAM AL-FALAH KOTA JAMBI - Azzaki, Muhammad Alfikri; Marwazi; Idarianty (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This research is motivated by the crucial role of teachers in optimizing students' Al-Qur'an memorization abilities, particularly Juz 30, at SMA Islam Al-Falah Jambi City. The primary focus of this study is to describe the strategies employed by Tahfidz teachers and to identify the supporting and inhibiting factors in the process of improving students' memorization skills. This study is a field research utilizing a qualitative descriptive approach. Data were collected through participant observation, in-depth interviews, and documentation studies. Data analysis was conducted through the stages of data reduction, data display, and conclusion drawing. The results indicate that: (1) Teacher strategies include pre-instructional steps such as providing motivation and reciting Asmaul Husna, followed by the implementation of Talaqqi, Bin Nazhar, and Takrir methods, and evaluation through the Tasmi’ system. (2) The quality of students' memorization is measured through quantitative and qualitative aspects. (3) Supporting factors include integrative school curriculum policies and the availability of audio murottal facilities. Meanwhile, the main inhibiting factors are low internal student motivation and limited instructional time allocation. This study concludes that the consistent application of the talaqqi and takrir methods is the key to maintaining the quality of students' Juz 30 memorization. Keywords: Learning Strategies, Tahfdiz Teacher, Al-Qur'an Memorization.